Enhancing the Export Competitiveness and Performance of Indonesian Halal Food Products in International Markets: The Influence of Economic, Demographic, and Trade Policy Factors - Nur Khayin Muhdlor; Irwandi Jaswir; Hendri Tanjung; Achmad Suryana (PT. Riset Press International, 2026)
This study investigates the determinants of Indonesia’s halal food export performance by focusing on destination-country characteristics and trade policy factors. This study employed a quantitative explanatory approach using balanced panel data from ten major destination countries of Indonesian halal food exports during the 2015–2024 period. Using balanced panel data from ten major destination countries over the period 2015–2024, the analysis employs panel data regression to examine the effects of Gross Domestic Product, population size, the proportion of Muslim population, and import tariffs on export performance. Model selection procedures indicate that the Fixed Effect Model is the most appropriate specification, allowing the analysis to control for unobserved country-specific characteristics that remain constant over time. The empirical findings show that Gross Domestic Product, population size, and the proportion of Muslim population in destination countries have positive and statistically significant effects on Indonesia’s halal food exports, suggesting that economic capacity, market scale, and preference compatibility jointly shape effective export demand. In contrast, import tariffs exhibit a negative and significant effect, confirming that higher trade barriers reduce export competitiveness and limit market access. Overall, the results indicate that Indonesia’s halal food export performance is determined by a combination of economic, demographic, and policy-related factors in destination markets. These findings provide empirical support for export strategies that prioritize economically strong markets while addressing tariff-related barriers to enhance Indonesia’s competitiveness in the global halal food industry. This study contributes to the halal trade literature by providing empirical evidence on the economic, demographic, and tariff-related determinants of Indonesia’s halal food export performance.